PERAN WALI DAN PERSETUJUAN MEMPELAI PEREMPUAN: Tinjauan atas Hukum Islam Konveensional dan Hukum Islam Indonesia - MA, Rahmawati, (EGALITA, 2008)
There is a wide-view in the sociey saying that women moslem according to Fiqh do not have freedom to dicide to whom they should marry. It is their father’s or wali who have authority to choose their husbands without their consents. This wiew based on an understanding of the concept of wali mujbir (forced wali). Moreover, due to the concept of wali mujbir, some people might argue that Islam has allowed forced marriage. Is this true? What is marriage law applied in Indonesia in which the biggest moslem population reside?